A socio-economic analysis of the wood supply ecosystem service in the Oued Beht watershed, Morocco. Issue 2 (1st February 2023) - Alaoui, Hassana Ismaili; Bouhatta, Mariyam; Ghazi, Souad; Brhadda, Najiba; Ziri, Rabea
ABSTRACT: Forest ecosystems provide a range of ecosystem services (ES) of which timber forest products (TFPs) represent a significant proportion of their economic value. This proportion is not entirely included in the total economic value of forest as there is a lack of data on the direct wood harvesting done by the local population which negatively affects the sustainable management of these resources. This study aims to emphasising the economic value of wood, based on two wood mobilisation systems (official and unofficial) which have been explored to determine the quantities extracted and their economic values. The results of study show that the wood generate an annual socio-economic value of more than 199 million MAD or 5, 981 MAD/ha/year. The right-use presents 66.80% of this value, more than 133 million MAD, followed by the auction with 31.09% and the illegal cuts with an amount of 4.2 million MAD. This work confirms the important role of this ecosystem service in the socio-economic life of local population. This information is useful towards emphasising need for participatory forest management to ensure the rational use of this ecosystem and the sustainability of its socio-economic values. This would ensure that community beneficiaries appreciate the economic role of forest products and the need to strengthen community governance structures in an endeavour to reduce conflict amongst beneficiaries. Therefore, we recommend institutionalising an equitable partnership between the users of space and the forest administration.